KONSEKUENSI HUKUM TINDAKAN HIRȂBAH (PELECEHAN SEKSUAL) DI INDONESIA: KAJIAN TERHADAP HUKUM PIDANA ISLAM DAN UNDANG-UNDANG INDONESIA - Ar Rasyid, Yanuriansyah; Djamaludin (Universitas Djuanda, 2024)
Hirabah is a term or concept in Islamic law that refers to acts of murder, robbery, and sexual assault. Incidents of rape and adultery often make headlines in Indonesia, but many rape victims feel disadvantaged by the judgments handed down by judges, which further victimize them. Additionally, certain articles have undergone an expansion of their meaning, particularly regarding adultery and rape, in order to minimize instances of rape. This study employs a qualitative research design, using approaches such as legal, conceptual, case-based, and comparative approaches. The findings reveal that the legal consequences for rape victims are deemed highly detrimental. This is evident in cases from Aceh, where a female rape victim received a whipping punishment that should not have been imposed on her. Furthermore, the common practice of seeking peaceful resolutions, such as marrying the victim to the perpetrator, is considered highly detrimental to the victims.